Hubungan Pengetahuan Dan Sikap Ibu Hamil Tentang Pemeriksaan Kehamilan Dengan Kunjungan Pemeriksaan Kehamilan Di Wilayah Kerja Puskesmas Gatak Sukoharjo - Prasodjo, Yoko Handry; , H.M. Abi Muhlisin, SKM., M.Kep; , Vinami Yulian, S.Kep., M.Sc (2016)
Pregnancy is a very sensitive period in a woman's life, which is prone to interference with physically and mentally. Pregnancy tests aim to detect any abnormalities or complications in early pregnancy. Some research suggests that maternal low knowledge and maternal bad attitude effect on the incidence of disorders during pregnancy. This study aimed at Correlation Knowledge and Attitudes About antenatal care with antenatal care visit in Gatak public health center Sukoharjo. This research is descriptive correlative with cross sectional approach. Samples were 58 pregnant women Trimester 3 (K3 and K4) recorded in Gatak Public health center Sukoharjo with accidental sampling techniques. The collecting data using questionnaires knowledge and attitudes as well as documentation in the form of books KIA pregnancy visit. The data were analyzed using Chi Square test. The result: the result of Chi Square relations with knowledge with antenatal visit obtained 2obs value of 12.013 (p-value = 0.002) so that H0 is rejected. The results of Chi Square test attitudes relationship with antenatal visit obtained 2obs value of 13.771 (p-value = 0.000) so that H0 is rejected. The conclusion of research is there is a correlation knowledge of pregnant women with antenatal care visit in Gatak Public Health Center, where the higher the mother's knowledge, the more complete examination of her pregnancy. The attitude of pregnant women associated with antenatal care visit of pregnant women in Gatak Public Health Center, where the better the attitude of expectant mothers, the more complete examination of her pregnancy.